#DictatorErdogan: How Social Media Bans Trigger Backlash. (2nd November 2022) - Miller, Andrew Cesare
ABSTRACT: Can authorities effectively shut down widely used social media platforms? This article theorizes that banning social media platforms with existing user bases triggers the psychological mechanism of reactance. Reactance motivates citizens to circumvent bans and ultimately results in intensified criticism of the censoring authorities on banned platforms. Reactance dynamics in response to social media bans are particularly relevant in countries with hybrid regimes – that is, regimes with both democratic and autocratic characteristics. Authorities in these countries generally allow widespread adoption of social media platforms. At the same time, they engage in temporary platform bans, usually to limit antiregime discourse at crucial political junctures such as elections. This combination of large user bases and temporary bans creates a "reactance equilibrium" in which there is high demand among citizens to access the restricted platforms. Unlike with censorship of traditional media such as television and print news outlets, the costs for citizens to circumvent social media bans are relatively low, which allows citizens to act on their reactance states. Drawing on a dataset of 15 million geolocated tweets, this article presents evidence of a censorship backlash to Turkey's March 2014 Twitter ban, which is considered among the first attempts to block a widely adopted social media platform. A synthetic control model and descriptive statistics reveal widespread circumvention of the ban. Furthermore, sentiment analysis shows that, in the wake of the ban, Twitter discourse became increasingly negative, especially toward the ban's main progenitor then-Prime Minister Recep Tayyip Erdogan.